Facilitating Non-School-Based Technical and Vocational Training for Disadvantaged Youths in South Africa - Mayombe, Celestin (Journal of Technical Education and Training, 2023)
Disadvantaged young people in Sub-Saharan Africa are the most stricken by unemployment because of their socio-economic background. Technical and vocational training programmes appear to be a remedy for their situation because the approaches to delivery are practice-oriented. Using experiential learning theory, the article examines the enabling factors for the effectiveness of non-school-based technical and vocational training on skills acquisition. The study used self-completion questionnaires, one-on-one semi-structured interviews and site observations to collect data from 512 young trainees, 24 training managers and 32 trainers. The findings reveal that the facilitation methods mostly used were the practical sessions in workshops, on-the-job training and workplace-based training. The author concludes that the practice-oriented methods were useful to empower the young trainees to acquire skills and abilities required for immediate employment. The practical and social implications of the findings are that, while disadvantaged youths cannot access and afford higher education, public and private sectors can remedy their situation by providing non-school-based technical and vocational training to help them enter the labour market.